Synthesis of silica-based solids by sol-gel technique using lemon bio-waste: Juice, peels and ethanolic extract - Cordero Castaño, Andres Felipe (2022)
After the consumption of the edible part, the citrus fruits are thrown into landfills generating serious pollution and disposal problems. Therefore, the use of citrus fruits for engineering applications has a dual purpose: to generate wealth from waste as an efficient reduction of solid waste. The main objective was to obtain silica-based materials from the precursor (TEOS), replacing acetic acid in acid hydrolysis with different parts of a lemon: peel, juice and peel ethanol extract. The solids obtained were characterized with different techniques such as TEM, SEM, FT-IR, potentiometric titration and XRD. TEM and SEM images were compared with the synthesized pure silica to contrast the morphology of the acidic hydrolysis with lemon. It can be concluded, in general terms, that the proposed objectives have been achieved, since materials were synthesized through a simple and fast method of obtaining, which allowed their inclusion in oxidic matrices. Until now, few attempts have been made to highlight the renewability of reagents used in the synthesis or to incorporate bio-based catalytic processes in larger scales. However, this research contributes to areas of environmentally friendly materials and synthesis, due to the synthesized solids could be used as a support in eco-catalysts.